News and information leadership in the digital age. Issue 11 (2nd November 2018) - Habel, Philip; Moon, Ruth; Fang, Anjie
ABSTRACT: This paper examines information networks on social media to draw conclusions about influence relationships among members of the mass media. The project considers social networks and information patterns using Twitter data, first at the newspaper level and second at the journalist level. Using a computational approach, we look for evidence of elite-directed information flows, as well as exploring whether we find evidence of an increase in the democratization of newsmaking. This study finds that elite voices continue to dominate information networks in the digital age; however, it also finds evidence that information can move expeditiously from journalists in local and regional outlets to elite ones, and vice versa. We move further to explore the content of tweets among the journalist network, finding that there are substantial, direct interactions among elite and regional and local journalists. Our results taken together uncover new network patterns and provide a novel insight on the role of information technologies in newsmaking in the digital age.